2002
DOI: 10.1038/sj.gt.3301670
|View full text |Cite
|
Sign up to set email alerts
|

An effective immunization and cancer treatment with activated dendritic cells transduced with full-length wild-type p53

Abstract: P53-based immunization is an attractive approach to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…Because both adenovirus-and p53-derived antigens are presented on the same DC, evaluation of antiadenovirus immunity may serve as a correlate for functional activity of DC. These data are consistent with the results obtained in animal models that showed a limited antiadenovirus response after immunization of mice with DCs transduced with different adenoviral constructs which did not affect antigen-specific CTL activity (14,36).…”
Section: Discussionsupporting
confidence: 82%
“…Because both adenovirus-and p53-derived antigens are presented on the same DC, evaluation of antiadenovirus immunity may serve as a correlate for functional activity of DC. These data are consistent with the results obtained in animal models that showed a limited antiadenovirus response after immunization of mice with DCs transduced with different adenoviral constructs which did not affect antigen-specific CTL activity (14,36).…”
Section: Discussionsupporting
confidence: 82%
“…This cell-based approach has been suggested as an effective technique for avoiding antiviral responses that occur with direct and repeated delivery of the virus itself. 32,33 There may be several reasons for this. First, as no free virus is administered, transduced cells escape the effects of pre-existing neutralizing antibodies directed against the viral capsid.…”
Section: Helper-dependent Adenovirus Enhanced Vaccine Responses a Harmentioning
confidence: 99%
“…The replication-deficient adenoviral vector has many superior characters including wide host range, high titer of amplification, ability to infect quiescent cells, and a lower potential for oncogenesis and teratogenesis than with retroviral vectors because there is no insertion of DNA into the host genome (Tauber and Dobner 2001). In 1999, Jesse, a patient with ornithine transcarbamylase (OTC) deficiency, died of multiple organ failure after his hepatic artery was injected with genetically altered adenovirus (Adv), so increasing attention has been paid to the effect of host immune responses against adenovirus-mediated gene therapy (Harvey et al 1999, Stein et al 2000, Rahman et al 2001, Nikitina et al 2002. It has been reported that intradermal administration of an adenoviral vector to humans induced local cellular responses and systemic Adv5-specific lymphocyte proliferation (Harvey et al 1999).…”
mentioning
confidence: 99%